Diferenças individuais em personalidade, coping e saúde geral: um estudo comparativo em duas cidades mineiras - Alana Augusta Concesso de Andrade (2012)
This research studied the individual differences in the five factors of personality, the ways of coping, and general health in two towns from Minas Gerais. The objective was to investigate the validity of the instrument of coping and the relation of this psychological process with personality and quality of life, and yet, to verify if these associations are replicated in two different contexts. It took part of the study 709 graduate students from private schools of Belo Horizonte and Sete Lagoas. The mean age were 25.13 years (SD=7.85) and there were 69.81% women. The majority of the economic classes of the sample were B and C, which represented 84.20%. The participants answered to the personality test NEO-FFI-R, the World Health Organization Quality of Life questionnaire WHOQOL, the Social Adjustment Scale and, the Ways of Coping Checklist WCC, besides those instruments, it was used, as a control variable, the Inferential Reasoning even items. The institutions spared classrooms for the collective evaluation of the participants. The results indicate evidence of construct validity of the WCC and the existence of three factors (problem focused coping, avoidance coping and, fantasy-religious coping). The three ways of coping were associated with the Social Adjustment Scale and also with all factors of personality, especially Neuroticism and Consciousness. Women and younger adults presented worse ways of coping, such as avoidance. The WCC also associated with all quality of life criteria and the problem focused coping were related to higher levels of health. The investigations of the two cities showed that the people from Belo Horizonte are less open to experience, avoid facing their problems and perceive worse quality of the environment, when they are compared to the people from Sete Lagoas. The predictor models of quality of life for each city showed that the personality traits have more explanation power than the ways of coping, especially Neuroticism and Extraversion. The ways of coping has prediction role only in the city of Belo Horizonte. It was applied, still, predictor models of coping in the two cities, which presented differences in the proportion of explained variance. However, they showed some common characteristics, such as the importance of Neuroticism and Extraversion. Openness, Agreeableness, and Consciousness have their contribution to the model as well, although, differently in each city. The variables sex and age have small or none role in the multiple regression. This thesis is limited by a specific sample, and it is concluded that the ways of coping and the personality traits are essential in order to determine human quality of life. The results contribute to the health care in clinics and institutions